The Relationship Between Physical Activity and Blood Pressure Status In Housewives with Hypertension in The Work Area of Samata Public Health Center - anshari, Nurul Khusnul Khotimah; Nurhidaya; Erni Astri Yani (Journal of Islamic Nursing, 2025)
Hypertension is one of the diseases with health problems that occur throughout the world. Hypertension is also a medical condition with a high prevalence. Hypertension can cause complications such as coronary heart disease, left ventricle hypertrophy, and stroke which are the highest carriers of death. One of the efforts in preventing hypertension is by doing physical activity such as morning walking, gymnastics, jogging and swimming. Through sports activities, the heart can work more efficiently, the frequency of pulse is reduced, but the pumping power of the heart is stronger. This study aims to determine the relationship between physical activity and blood pressure status in housewives with hypertension in the working area of the Samata Health Center. This study uses quantitative research design analytical survey with cross sectional design approach, Location of Research Study in the Work Area Health Center Same District Gowa. Technique taking sample with method non probability sampling with method total sampling with total 33 people. The chi-square test results obtained p-value of 0.033 with a significance level of <0.005. The p-value (0.033) is smaller than 0.05 meaning that there is a relationship between physical activity and blood pressure status in housewives. There is a significant relationship between physical activity and blood pressure status among hypertensive housewives. Regular physical activity can help control blood pressure and prevent complications like heart disease and stroke.   Keywords: : Physical Activity, Blood Pressure Status, Hypertension